Consumer Protection in the Electricity Sector - Bhavesh Acharya (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2023)
With the constant evolution of the country’s electricity regulations, consumer protection in the Indian electricity sector has grown dexterously. Every Electricity Act that has been passed throughout the years has increased the extent of consumer protection. During the last two decades, the Country has witnessed notable improvements, particularly in the infrastructure, power generation, and most importantly consumer welfare. The Electricity Act of 2003, in its numerous clauses and other government legislation and policy documents, clearly state that efficiency consumer protection, and welfare are the primary goals for achieving real reforms in the electricity sector. The government, through this Act, has provided several ways to promote consumer awareness. The Act has also established a comprehensive two-tier grievance redressal mechanism consisting of CGRF at the primary level and Ombudsman at the State level to protect consumers from the tiring traditional resolution process. To ensure that the consumers benefit from the regulations, the Act also provides for minimum standards in the form of Standards of Performance which are required to be met by the licensees.